Supermarkets and household food acquisition patterns in Vietnam in relation to population demographics and socioeconomic strata: Insights from public data - Trinh, H.T.; Burra, Dharani Dhar; Simioni, M.; Haan, Stef de; Huynh, T.T.; Huynh, T.V.; Jones, A.D. (Frontiers Media, 2020)
Food environments in Southeast Asia's emerging economies are rapidly evolving, alongside fast-paced socioeconomic and demographic changes. The widespread expansion of supermarkets and parallel restructuring of traditional markets in Vietnam are likely to impact patterns of household food acquisition. Using provincial-level time series data on the abundance of supermarkets and multiyear household survey data, this paper examines the impact of the differential country-wide presence of supermarkets with indices of food quality and quantity acquired by households. We classified provinces into three clusters based on the number of supermarkets: high (HighSM), medium (MedSM), and low (LowSM). We found that a higher number of supermarkets associated with the exceedable Vietnamese recommendation composition of macronutrients at the household-level, but not food quantity. Households with higher per capita food expenditure in HighSM provinces tended to procure foods with higher protein content and lower shares of fat and carbohydrate as compared to similar households in the others provinces. Ethnic minority households in MedSM clusters obtained food with lower carbohydrate and higher fat:protein ratios in comparison to ethnic majority households. Additionally, larger-sized households in HighSM provinces typically bought foods with higher fat shares than smaller-sized households. In contrast, in MedSM and LowSM provinces, larger-sized households typically procured foods with higher protein and lower fat shares. The diversity of foods obtained by households in MedSM and LowSM provinces decreased over time. Within the Midlands and Northern Mountains Area we observed a decrease in the diversity of food acquired among households in the LowSM clusters. This study elucidates potential impacts of the supermarket expansion on household food baskets. Insights from this study can be used to provide evidences for policy recommendation and to design and target interventions aimed at strengthening food environments to address the challenge of the double burden of malnutrition in the country.